6.9k views
3 votes
Simplify.14+{−2+3[1+3(− 6−2)]}

User Peixu Zhu
by
5.1k points

1 Answer

0 votes

We must simplify the next


14+\mleft\lbrace-2+3\lbrack1+3(-6-2\mright)\rbrack\rbrace
\begin{gathered} 14+\lbrace-2+3\lbrack1+3(-6-2)\rbrack\rbrace \\ =14+\lbrace-2+3\lbrack1+3(-8)\rbrack\rbrace \\ =14+\lbrace-2+3\lbrack1-24\rbrack\rbrace \end{gathered}
\begin{gathered} =14+\lbrace-2+3\lbrack-23\rbrack\rbrace \\ =14+\lbrace-2-69\rbrace \end{gathered}
\begin{gathered} =14+\lbrace-2-69\rbrace \\ =14-71 \\ =-57 \end{gathered}

User Dmitry Sazonov
by
4.9k points